(untitled) (Sebha University Conference Proceedings, 2024)
Class imbalance refers to a scenario where the quantity of data in the minority class is significantly lower than that in the majority class, resulting in challenges in classification. To address this issue, this study tackles the challenge of class imbalance in breast cancer prediction using a dataset from the Sabha Center for Oncology Treatment in southern Libya. The research investigates the impact of eight different sampling techniques, including SMOTE, Adasyn, and NearMiss, when combined with Random Forest classification. The findings reveal that integrating SMOTE with Random Forest significantly outperforms other model configurations, resulting in a 21% increase in accuracy for predicting malignant samples and reaching a peak recall of 96%. This study demonstrates the importance of addressing class imbalances in medical datasets to improve the effectiveness of breast cancer prediction models.